Diamang. Estudo do Património Cultural da Ex-Companhia de Diamantes de Angola - Museu Antropológico (Outros Títulos, 2019)
The transformations of society contemporary and particularly those resulting from the revolution which took place on 25 April 1974 were decisive in taking on a new relationship between Portugal and the young African Portuguese speaking countries. A secular history united us, marked by political, economic, social and cultural ties that need to be recontextualized without undermining the exceptional common cultural heritage. In this area, the Anthropological Museum of the University of Coimbra timely recognized the importance of the collection - bibliographic, ethnographic and audio-visual - resulting from the scientific and cultural activity developed by the former Diamang and, at the time (1986), property of the Portuguese Society of Enterprises. [...]Motivated by these premises, we formalized the research project «Study of the Cultural Heritage of the former Diamond Company of Angola: a contribution to inter-ethnic dialogue and rapprochement with Portuguese-speaking African Countries», submitted to the National Board of Scientific and Technological Research and by the same body approved at the end of 1987. The main objective of the proposal was to "scientifically investigate and pedagogically value the ex-Diamang's estate", which should be immediately transferred to the Anthropological Museum of the University of Coimbra, since it was the empirical basis of the studies. planned. Difficulties in implementing the project were decisive in the orientation and objectives of this publication as a research tool, perhaps the first to be considered by the researcher in addressing the estate. This is admittedly a formal survey of the material that, since 1989, been available to the project team, i.e. the collection ethnographic, the core designated audio-visual and important set of reports and memos relating to activities scientific and cultural of the Diamond Company of Angola. This situation justifies the incidence in those, in contrast to the brief note on the bibliographic material, since it was only transferred to Coimbra in 1993. Their size and recognized importance, even at the international level, led us to act immediately in the technical fields of preservation and registration - practice, moreover, followed in the remaining nuclei, according to the specificity of the support materials and state of conservation - delaying, for obvious reasons, the exhaustive publication of the bibliographic catalog. The publication Diamang: A Study of the Cultural Heritage of the former Angolan Diamond Company should therefore be understood as a thematic inventory through which the valuable and sometimes unpublished documentation gathered over the last decades has been methodologically explicit remarkable time of the Portuguese colonial phenomenon. It is, therefore, a complex and multidisciplinary archive of documentary sources, potentially subsidiary to various scientific disciplines, but itself by the nature of prevailing ideology, which may be the object of study. [Manuel Laranjeira Rodrigues de Areia, Project Responsible Researcher]